Developing Two study Units in the Social and National Education According to the Generative Constructivist Model and Measuring their Effects on Improvement of Higher Thinking Skills and Life Skills for Students of Basic Stage - Zaid S. Al-Edwan; Ahmed I. Daoud (Sultan Qaboos University, 2016)
The purpose of this study was to develop two study units in the social and national education according to the generative constructivist model and to measure their effects on thinking skills and life skills of the basic stage students. Study sample consisted of 60 third-grade students from AL-Yadodah school (Jordan) in the year 2013-2014. To achieve the objectives of the study, a higher thinking skills and life skills tests were prepared. The researchers developed the two study units according to the generative constructivist model. The study results showed that the experimental group outscored the control group on both the higher thinking skills, and on the post testing of the life skills.